Forecasting the yield curve with the arbitrage-free dynamic Nelson-Siegel model: Brazilian evidence - Jo\~ao F. Caldeira; Guilherme V. Moura; André A. P. Santos; Fabricio Tourrucôo (EconomiA, 2016)
We assess the extent to which the imposition of a no-arbitrage restriction on the dynamic Nelson–Siegel model helps obtaining more accurate forecasts of the term structure. For that purpose, we provide an empirical application based on a large panel of Brazilian interest rate future contracts and test for differences in forecasting performance among alternative benchmark specifications including the random walk, vector autoregressions, and the dynamic Nelson–Siegel. We show empirically that the arbitrage-free Nelson–Siegel model is able to outperform all other benchmark models when longer forecasting horizons are taken into account. – – Neste artigo avaliamos em que medida a imposiç\~ao de uma restriç\~ao de n\~ao arbitragem na vers\~ao dinâmica do modelo de Nelson–Siegel ajuda a obter previs\~oes mais precisas da estrutura a termo. Para isso, realizamos uma aplicaç\~ao empírica envolvendo um amplo conjunto de taxas de juros de contratos de DI-futuro negociados na BM&F Bovespa. Os resultados s\~ao comparados com os modelos competidores mais amplamente usados, incluindo o random walk, vetores autorregressivos e o modelo dinâmico de Nelson–Siegel. Os resultados encontrados mostram evidências de que o modelo de Nelson–Siegel com condiç\~ao de n\~ao arbitragem é capaz de superar os modelos benchmarks quando se consideram horizontes de previs\~ao mais longos em todo o espectro de maturidades analisadas.
Keywords: 330; Yield curve; Arbitrage-free Nelson-Siegel model; Dynamic factor models; Kalman filter